Promoting gender responsiveness in teaching physical education - Lalog, Ryan Cazel (Physical Education and Sports: Studies and Research, 2025)
Background: Implementing gender policies in physical education at Batangas State University remains moderate, with challenges in ensuring gender-responsive and equitable activities for male and female students. Issues such as students' self-confidence, self-perception, and limited gender mainstreaming strategies and resources hinder the development of a more inclusive learning environment. Objectives: This study examined gender policy implementation, the use of strategies and resources in various physical education activities, differences in male and female instructors' assessments, challenges in gender mainstreaming, and the development of gender-responsive activities. Methods: A descriptive research method was used, collecting data from 105 university physical education instructors (77 males, 28 females) through a researcher-made survey questionnaire. Results: Findings revealed that gender policies were moderately implemented (mean score: 3.47), while both male (3.67) and female (3.63) instructors highly utilized strategies and resources in physical fitness, rhythmic activities, individual and dual sports, and team sports. No significant differences were observed in male and female educators' assessments, indicating shared perspectives on gender mainstreaming. Conclusions: The study emphasizes the need for more vigorous policy enforcement and improvements in sports-related content to enhance gender inclusivity. Addressing self-confidence, self-perception, and individual differences is crucial for fostering equitable learning experiences. Universities should provide continuous professional development for PE instructors on gender-sensitive teaching strategies. Future research should explore the long-term impact of gender-responsive approaches on student engagement, performance, and overall well-being in physical education.